Inhaled isopropyl alcohol for nausea. Issue 11 (November 2017) - Neff, Laurel; Thompson, Richard; O'Mara, Heather; Maurer, Doug; Butsch, Meagan; Dalton, Heather
Abstract : N/A: Beadle KL, Helbling AR, Love SL, April MD, Hunter CJ. Isopropyl alcohol nasal inhalation for nausea in the emergency department: a randomized controlled trial. Ann Emerg Med . 2016; 68(1):1–9.e1.